Pre-Visit Perceives Imager: The Importance of Tourism Communication in the Digital Age - Febrian Febrian (Universitas Indonesia, 2021)
AbstractThis paper examines tourism communication that shows the importance of information on a destination in various platforms and also the role of forming a pre-visit image that is built in the minds of potential visitors. Promotional strategies can also reflect on the pre-visit perceived image as the main thing in seeing a destination. The development of media and platforms used to access pre-visit information apart from being a promotional media is also important to be seen as an initial filter for potential visitors before determining which destination they interested in.Keywords: Pre-visit, Tourism Communication, digital platform